Experimental analysis of ballistic trauma in a human body protected with 30 layer packages made of biaxial and triaxial Kevlar® 29 fabrics - Justyna Pinkos; Zbigniew Stempien; Anna Smędra (Defence Technology, 2023)
Behind armour blunt trauma (BABT) is a body injury resulting from the deformation of the back surface of armour as a result of a bullet impact. In the case of textile body armour, the severity of the injury may depend on the material of the fibres, but also on the geometric structure of the fabric. The article focuses on experimental research into injuries of the human body protected by ballistic packets made of biaxial and triaxial fabrics, during a non-penetrating impact from a Parabellum 9 mm × 19 mm Full Metal Jacket (FMJ) bullet, at a speed of 406 ± 5 m/s. In experimental research, the fabrics had a comparable surface weight and were made of the same Kevlar® 29 yarn. The ballistic packages were made of 30 layers. As part of the work, a physical model of the human body was developed. The human body model consisted of a model of the heart, lungs, and skeletal and muscular systems. During the bullet impact, the pressure forces were recorded using sensors located at selected points of the human body. The bullets hit five selected places on the body that were considered critical, from the point of view of maintaining a human’s vital functions. It was found that, during firing, pressure increases both at the site of impact and in the internal organs, which can lead to multi-organ damage. As a result of the experimental analysis, it has been shown that the pressures exerted on specific organs are always lower in the case of body protection with a ballistic packet made of triaxial fabrics, compared to a packet made of biaxial fabrics.